Evaluation of Effect of Quality Standards on Quality of Education in Public and Punjab Education Foundation Funded Schools at Secondary Level - Sabir Hussain,; Masood Ahmad,; Sobia Altaf,; Muhammad Farooq Ahmad, (JCTE, 2024)
This research was conducted to evaluate the effects of quality standards on the quality of education in public secondary and Punjab Education Foundation Funded Schools against the Quality Standards provided by School Education at the secondary level. Eighteen schools were selected from each district of Punjab province, of which 9 were public and 9 were Punjab Education Foundation schools. Then 102 teachers of Public Secondary and 102 teachers of Punjab Education Foundation were randomly selected from these schools. A total of 15 questions were asked from the teachers using a 5-point Likert scale, including about quality of school assessment, quality of management, quality of teachers, quality of school infrastructure and quality of monitoring. The mean, standard deviation, t-test and F-test were used for this. The results obtained were compared with previous research and discussed deeply. It was concluded that the quality standards issued by the Ministry of School Education were being followed more by the public schools. Quality of monitoring, management, teaching staff quality, assessment, and school infrastructure were found to be good in public schools. It is recommended that the quality of monitoring in schools should be raised; as seen in public schools, the quality of assessment should also be raised.